SLR ABOUT THE COSTS OF PRIVATE BLOCKCHAIN TECHNOLOGY FOR BUSINESSES - Nagy, Péter; Nagy, Adrián Szilárd (Economica, 2024)
Since the appearance of Bitcoin (2009), blockchain technology has been used in many fields. Companies use it for financial services, goods tracking, data authentication and secure storage, among other things, in order to make their operations more transparent and efficient. This technology has revolutionized the data management and transaction processing, but the associated costs are also significant and relevant to understand. The costs of blockchains vary and depend on the type of blockchain and how it is used. In this article, we examine the costs of using blockchain technology based on international literature, studies and reports with systematic literature review. In the results the range of possibilities offered by technology is presented, as well as the technology related cost types, and expenditures what companies have to deal with.